Factors affecting antenatal care attendance in Soweto, Johannesburg: The three-delay model - Nellie Myburgh; Thabisile Qwabi; Lunghile Shivambo; Lerato Ntsie; Andile Sokani; Maria Maixenchs; Isaac Choge; Sana Mahtab; Ziyaad Dangor; Shabir Madhi (AOSIS, 2024)
Background: Antenatal care remains critical for identifying and managing complications contributing to maternal and infant mortality, yet attendance among women in South Africa persists as a challenge. Aim: This study aimed to understand the challenges faced by women attending antenatal care in Soweto, Johannesburg, using the three-delay model. Setting: This study was conducted in Soweto, Johannesburg. Methods: An exploratory, descriptive and qualitative research design was used, and in-depth interviews were conducted with 10 pregnant women and four women who had recently given birth. Results: Findings indicate delays in seeking care due to factors such as pregnancy unawareness, waiting for visible signs, and fear of human immunodeficiency virus (HIV) testing. Challenges such as transportation difficulties, distance to clinics, and facility conditions further impeded the initiation of antenatal care. Late initiation often occurred to avoid long waits, inadequate facilities, language barriers and nurse mistreatment. Conclusion: From this study, we learn that challenges such as unawareness of pregnancy, cultural notions of keeping pregnancy a secret, fear of HIV testing, long waiting lines, high cost of transportation fees, clinic demarcation, shortage of essential medicines, broken toilets and verbal abuse from nurses have delayed women from initiating antenatal care early in Soweto, Johannesburg. Contribution: Challenges of women with antenatal care attendance in South Africa must be addressed by implementing community-based health education interventions, institutionalising HIV psycho-social support services and improving quality of antenatal care services in public health facilities.